2015
DOI: 10.1097/md.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Diagnosis of Tuberculous Lymphadenitis in a Tuberculosis Low-Burden Country

Abstract: The aim of this article is to describe epidemiological and clinical data of patients with tuberculous lymphadenitis (TL) and evaluate the yield of the diagnostic techniques employed.Retrospective observational study was performed at the Vall d’Hebron University Hospital, Barcelona, Spain. All adult patients with confirmed TL (microbiologically) or probable TL (suspected by clinical presentation, cyto/histopathological features, and clinical improvement after specific treatment) diagnosed from January 2001 to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 19 publications
3
34
0
6
Order By: Relevance
“…In published data, AFB detection ranged from 0.8% to 48.5%, while culture positivity ranged from 20% to 62% (10)(11)(12)(13)(14)(15)(16)(17). When these results are compared with fineneedle aspiration results for peripheral lymph nodes and EUS studies for mediastinal lymph nodes, sensitivities and specificities are similar (2,(18)(19)(20)(21). As a result, conventional microbiological methods have low diagnostic sensitivity for the diagnosis of MTLA, mostly due to a low burden of bacilli and insufficient sample amount (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In published data, AFB detection ranged from 0.8% to 48.5%, while culture positivity ranged from 20% to 62% (10)(11)(12)(13)(14)(15)(16)(17). When these results are compared with fineneedle aspiration results for peripheral lymph nodes and EUS studies for mediastinal lymph nodes, sensitivities and specificities are similar (2,(18)(19)(20)(21). As a result, conventional microbiological methods have low diagnostic sensitivity for the diagnosis of MTLA, mostly due to a low burden of bacilli and insufficient sample amount (22).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly affected lymph nodes (LNs) are the cervical, followed by mediastinal, supraclavicular, and inguinal LNs (2). In the International Standards for Tuberculosis Care it is recommended that microbiological confirmation must be made, and diagnostic materials should be obtained for microbiological and histopathological evaluation for diagnosis of EPT (3).…”
Section: Introductionmentioning
confidence: 99%
“…In 8 studies, there was information on HIV infection of which 1 study solely included HIV patients [25]. Three studies reported other comorbidities than HIV [20, 26, 29]. …”
Section: Resultsmentioning
confidence: 99%
“…Five articles had data on patient delay [20, 22-25], three on health care delay [19, 26, 27], and three on total delay [21, 28, 29]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation